Rome, Colosseum square and NE slopes of the Palatine hill: toward an integrated 3D system for stratigraphic data management and ancient urban landscape reconstruction - Clementina Panella; Emanuele Brienza; Lorenzo Fornaciari (Groma, 2021)
The investigations carried out in the valley of the Colosseum and on the NE slopes of the Palatine have disclosed a complex sequence of urban and monumental interventions whose documentation has inevitably produced a vast amount of data that is difficult to manage without the aid of an information system. With the recent development of new applications, it is possible to create a system for the integration and visualisation of archaeological data, both in two and three-dimensional format, and to experiment with new criteria and methods for the combined and effective use of documents of a different nature.